Bidirectional pharmacokinetics of doravirine, tenofovir, and feminizing hormones in transgender women (IDentify): A randomized crossover trial - Kevin Lam; Walter K. Kraft; Tingting Zhan; Edwin Lam (Wiley, 2024)
Abstract Transgender women may have concerns of drug interactions between feminizing hormone therapy (FHT) and antiretrovirals, leading to nonadherence. This randomized, three‐period crossover, open‐label, phase I trial assessed the effects of doravirine (DOR) and tenofovir disoproxil fumarate (TDF) on the pharmacokinetics (PKs) of estradiol, spironolactone, and total testosterone and vice versa in healthy transgender women. Volunteers were randomized 1:1 into two sequences containing three treatment groups (DOR, lamivudine [3TC], and TDF alone; estradiol, spironolactone, and placebo; and DOR/3TC/TDF, estradiol, and spironolactone). Eight subjects enrolled in the study and six had completed all study periods. The geometric mean ratios for DOR area under the concentration‐time curve from zero to last measured concentration (AUC0‐last), maximum concentration (Cmax), and concentration at 24 h (C24) were similar. However, tenofovir (TFV) AUC0‐last, Cmax, and C24 moderately increased by 14%-38%. Last, estradiol AUC0‐last, Cmax, and C24 were increased by 10%-13%. Whereas most 90% confidence intervals did not meet the bioequivalence bounds of 80%-125%, the point estimates fell within the intervals. Log‐transformed DOR, TFV, and estradiol PK parameters computed with and without co‐administration were not statistically different (p > 0.05). There were no serious adverse events. There is not a clinically significant impact of FHT on DOR/TFV PKs. Similarly, there is no observed impact on estradiol PKs and total testosterone following use of DOR/3TC/TDF.